2014
DOI: 10.1152/japplphysiol.00008.2013
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric exercise in rehabilitation: safety, feasibility, and application

Abstract: This nonexhaustive mini-review reports on the application of eccentric exercise in various rehabilitation populations. The two defining properties of eccentric muscle contractions--a potential for high muscle-force production at an energy cost that is uniquely low--are revisited and formatted as exercise countermeasures to muscle atrophy, weakness, and deficits in physical function. Following a dual-phase implementation, eccentric exercise that induces rehabilitation benefits without muscle damage, thereby mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
156
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 112 publications
(169 reference statements)
4
156
0
Order By: Relevance
“…We discount both of these alternatives, but they certainly merit further study. First, the kinetic energy at take-off [about 0.023 J for zebra finches and 0.042 J for diamond doves (Provini et al, 2012)] is greater than the kinetic energy at touchdown (about 0.005 J for zebra finches and 0.018 J for diamond doves), and vertebrate muscle is capable of producing more force during active lengthening than during shortening, and is capable of absorbing more negative than positive work (Hill, 1953;LaStayo et al, 2014). Second, we estimate that the rate of change of kinetic energy within a wingbeat in zebra finches varied from about 0.01 to 0.0017 J from W -3 to W -1 and was 0.046 J during ground contact from touch-down to the return to support of body weight, while for diamond doves it was 0.0056 to 0.03 J from W -3 to W -1 , and 0.042 J during ground contact from touchdown to the return to support of body weight.…”
Section: Research Articlementioning
confidence: 99%
“…We discount both of these alternatives, but they certainly merit further study. First, the kinetic energy at take-off [about 0.023 J for zebra finches and 0.042 J for diamond doves (Provini et al, 2012)] is greater than the kinetic energy at touchdown (about 0.005 J for zebra finches and 0.018 J for diamond doves), and vertebrate muscle is capable of producing more force during active lengthening than during shortening, and is capable of absorbing more negative than positive work (Hill, 1953;LaStayo et al, 2014). Second, we estimate that the rate of change of kinetic energy within a wingbeat in zebra finches varied from about 0.01 to 0.0017 J from W -3 to W -1 and was 0.046 J during ground contact from touch-down to the return to support of body weight, while for diamond doves it was 0.0056 to 0.03 J from W -3 to W -1 , and 0.042 J during ground contact from touchdown to the return to support of body weight.…”
Section: Research Articlementioning
confidence: 99%
“…2 In general, different types of exercise therapy are used to enhance functional activity, muscle strength, and mobility in patients with MS. [3][4][5] The results of these studies showed not only that aerobic exercises can cause physiologic changes 5 and improve ambulatory function and fatigue 6 but also that strength training exercise can increase muscle fiber size 7 and muscle strength 3 and improve functional activities and balance in patients with MS. 4 In a systematic review study, the authors suggested that "resistance training of moderate intensity seems to be well tolerated and to have beneficial effects on patients with MS." 8(p51) Endurance and resistance training sessions have been designed based on concentric contraction (contraction accompanied by shortening of muscle length, eg, uphill walking) of the involved muscles, which causes muscular hypertrophy and improves functional activity. 9 It must be pointed out that these types of exercises are generally considered high-intensity training (60%-80% of the maximum voluntary contraction force), which may tire out patients with MS. 10 However, some research has shown that eccentric exercise training (contraction accompanied by elongation of muscle length, eg, downhill walking), compared with concentric exercise, may improve balance in elderly people 11 and increase muscle strength in patients with Parkinson disease 12 and MS. 13 This is due to its potential for high muscle force production at a uniquely low energy cost 14 so that downhill walking (as a model of eccentric exercise) requires less energy cost than uphill walking (as a model of concentric exercise). 15 However, eccentric activity of muscles is necessary to control human body movement against gravity.…”
mentioning
confidence: 99%
“…12 men reported no difference. Reported intensity in concentric exercises was 14.6 ± 4 (BORG-Scale, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In women, no myocardial infarct could be detected. Blood pressure was increased in 3 and an Arrhythmia was four times reported.…”
Section: Resultsmentioning
confidence: 99%